Assessing repeated-sprint ability in division i collegiate women soccer players - Lockie, R. G.; Liu, T. M.; Stage, A. A.; Lazar, A.; Giuliano, D. V.; Hurley, J. M.; Torne, I. A.; Beiley, M. D.; Birmingham-Babauta, S. A.; Stokes, J. J.; Risso, F. G.; Davis, D. L.; et al. (The Journal of Strength and Conditioning Research, 2020)
Repeated-sprint ability (RSA) is a key component of soccer, and is the capacity to repeatedly produce near-maximal to maximal sprints with short recovery periods. Repeated-sprint ability has received little analysis in collegiate women soccer players. The purpose of this study was to investigate relationships between RSA and tests of soccer-specific performance. Nineteen players from the same Division I collegiate women's soccer team were recruited. The RSA test consisted of six 20-m sprints completed on 15-second cycles. The measurements taken were total time (TT) and percent decrement (PD; percent change from first to last sprint). Subjects also completed tests of: lower-body strength (1 repetition maximum [1RM] back squat); jump performance (vertical and standing long jumps); linear (0-5, 0-10, and 0-30 m sprint intervals) and change-of-direction (505 from each leg) speed; and soccer-specific fitness (Yo-Yo intermittent recovery test level 1 [YYIRT1]). Pearson's correlations (p = 0.05) were used to calculate relationships between RSA TT and PD with the performance tests. Total time exhibited significant relationships with the 0-10 (r = 0.50) and 0-30 m (r = 0.71) sprint intervals, and the left-leg 505 (r = 0.57). However, lower-body strength measured by the 1RM back squat and jump performance did not relate to TT. Percent decrement correlated only with the left-leg 505 (r = 0.53) and no other performance test. This included the YYIRT1, although both PD and YYIRT1 performance are limited by fatigue. The results from this study indicated that faster linear sprinting speed could positively influence RSA in Division I collegiate women soccer players.